Estudio genotóxico de una bebida experimental de quinua, kiwicha y kañiwa - Huaman, Francia D.P. (2014)
Genotoxic evaluation is an important step for a product that is aimed for human consumption. A beverage composed of pseudocereals with highly nutritious elements like quinua (Chenopodium quinoa Willd.), kiwicha (Amaranthus caudatus L.) and kañiwa (Chenopodium pallidicaule Aellen) was prepared to reduce lipid contents in a group of volunteers. The objective of the present study is to evaluate the genotoxic potential of an experimental beverage using two in vitro tests that have been validated by international agencies. For the Ames test, two strains of Salmonella typhimurium (TA98 and TA100) with and without microsomal fraction (S9) were used. Four doses of the beverage were tested and also a possible protective effect (same four doses of beverage added to plates with mutagens). Cultures of binucleated lymphocytes and five doses of the beverage were used for the micronucleus test. Both Ames and the micronucleus tests showed the beverage has not genotoxic effect in all tested doses. However, in evaluating the possible protective effect of the beverage, it would be evident that on the contrary, the mutagenic effect of mutagens used for each strain is enhanced. These results suggest that additional tests should be performed to check the genotoxic potential of this beverage before consumption.